Integrating research infrastructures into infectious diseases surveillance operations: Focus on biobanks - Plebeian B. Medina; Jennifer Kealy; Zisis Kozlakidis (Elsevier, 2022)
Technological advances in the first two decades of the 21st century have profoundly impacted medical research in many ways, with large population cohorts, biological sample collections and datasets through biobanks becoming valued global resources to guide biomedical research, drug development, and medical practice. However, in order for biobanks to maximize their impact and scientific reach of their resources, they would need to act within a complex network of infrastructures and activities. Therefore, different ways have emerged in which biobanks, including those for infectious diseases, can emerge as (part of) infrastructures, integrate within existing ones, or become an independent, yet an interoperable component of the existing infrastructural landscape. However, there has been a limited understanding and study of such mechanisms to date. This perspective aims to address this knowledge gap and illustrates these three high-level ways in which such infrastructures could integrate their activities and identifies the necessary key pre-conditions for doing so, while drawing from specific examples.